Ethnomathematics Exploration of Traditional Bugis-Makassar Food Based on The Mathematization of Iceberg Realistic Mathematics Education - Ja’faruddin; Muhammad Ammar Naufal; Hisyam Ihsan (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This study aims to explore geometric ideas in traditional food called Tumpi-Tumpi, a typical Bugis Makassar cuisine, and to develop problem-solving abilities using the Iceberg Realistic Mathematics Education (RME) model. This study used a qualitative study with descriptive exploration. Data was collected through observation, interviews, and documentation. Based on the design of Miles and Huberman, the data analysis technique consisted of data reduction, data presentation, and conclusion/verification. According to data collection results, the traditional Bugis-Makassar cuisine Tumpi-Tumpi contains ethnic mathematical components (geometrical concepts), namely, the plane figure of an equilateral triangle, and is used to solve mathematical problems. The Iceberg RME math technique utilized